Impact of serum sodium trajectory on 30-day mortality in traumatic brain injury patients: insights from a retrospective cohort study using MIMIC-IV database - Huang, Shuangshuang; Huang, Songmin; Wang, Wulei; Li, Zhimin; Liu, Yingjun (Frontiers in Neurology, 2025)
BackgroundHypernatremia is frequently encountered in individuals with traumatic brain injury (TBI), and research has demonstrated a correlation between serum sodium levels and patient outcomes in TBI cases. This study aims to explore the temporal patterns of serum sodium concentrations and assesses their prognostic significance in TBI patients.MethodsThis study employed data sourced from the database of Medical Information Mart for Intensive Care IV (MIMIC-IV). We applied a latent growth mixture model (LGMM) to construct the serum sodium trajectories of TBI patients within the first 96 h of their intensive care unit (ICU) stay, based on mean serum sodium measurements taken at 24-h intervals. Subsequently, Cox regression models were employed to analyze the associations among initial serum sodium levels, serum sodium trajectories, and mortality outcomes of 30 and 90 day.ResultsA total of 852 TBI patients were included, and the LGMM model categorized serum sodium trajectories into 4 classes. Significant differences in prognosis were observed between the different grades of TBI patients, with the worst prognosis for patients with TBI in Class 2 (slow-growth type) compared to Class 1 (normal stable type) and no significant difference in mortality for the remaining grades. In addition, after adjusting for confounding factors, high first serum sodium levels were related to higher 30-day (HR = 2.14, 95% CI: 1.13–4.04, p = 0.019) and 90-day (HR = 2.22, 95% CI: 1.21–4.08, p = 0.01) mortality rates in TBI patients.ConclusionBoth first-time serum sodium and serum sodium trajectory were independent influences on the prognosis of TBI patients. Thus, clinicians should closely monitor serum sodium in TBI patients and adjust treatment strategies based on its dynamic changes.